Análisis de factores de riesgo y su influencia en la calidad de leche cruda en unidades de producción en el cantón Babahoyo Provincia de Los Ríos - Angulo Tomalo, Emy Juliany (2023)
Milk is a source of energy and mineral proteins that are essential for human develop-ment, therefore it is necessary to ensure its safety and guarantee food security. In this present investigation, a total of 11 analyzes were carried out on production units located in Babahoyo Province of Los Ríos, which were evaluated following the estab-lished criteria such as risk factors and quantitative quality parameters. The main objec-tive was to determine if the risk factors are an indicator for the variables analyzed when obtaining the samples and taking them to laboratory studies in which the following was verified: Regarding the presence of antibiotics in raw milk, it was determined that of 100% of the 11 farms analyzed, 72% were positive for antibiotics while 27% were negative for the same parameter. In the test carried out for peroxide in raw milk, there is 0% as a result of the analysis. The density and temperature of the raw milk was evaluated through the alcohol test, resulting in the 11 farms complying with the NTE INEN 9:2012, which mentions that its density must be between 1,029 to 1,033 g/ml, as -To the protein stabil-ity, 8 positive and 3 negative for this parameter were obtained, resulting in the first 8 farms being positive, having a percentage of 100% each and the last 3 samples were negative, therefore their incidence is 0. %.